Propagation of Spermatogonial Stem Cell-Like Cells From Infant Boys - Dong, Lihua; Kristensen, Stine Gry; Hildorf, Simone; Gul, Murat; Clasen-Linde, Erik; Fedder, Jens; Hoffmann, Eva R.; Cortes, Dina; Thorup, Jorgen; Andersen, Claus Yding (Frontiers in Physiology, 2019)
Background Gonadotoxic treatment of malignant diseases as well as some non-malignant conditions such as cryptorchidism in young boys may result in infertility and failure to father children later in life. As a fertility preserving strategy, several centers collect testicular biopsies to cryopreserve spermatogonial stem cells (SSCs) world-wide. One of the most promising therapeutic strategies is to transplant SSCs back into the seminiferous tubules to initiate endogenous spermatogenesis. However, to obtain sufficient numbers of SSC to warrant transplantation, in vitro propagation of cells is needed together with proper validation of their stem cell identity. Materials and Methods A minute amount of testicular biopsies (between 5 mg and 10 mg) were processed by mechanical and enzymatic digestion. SSCs were enriched by differential plating method in StemPro-34 medium supplemented with several growth factors. SSC-like cell clusters (SSCLCs) were passaged five times. SSCLCs were identified by immunohistochemical and immunofluorescence staining, using protein expression patterns in testis biopsies as reference. Quantitative polymerase chain reaction analysis of SSC markers LIN-28 homolog A (LIN28A), G antigen 1 (GAGE1), promyelocytic leukemia zinc finger protein (PLZF), integrin alpha 6 (ITGA6), ubiquitin carboxy-terminal hydrolase L1 (UCHL1) and integrin beta 1 (ITGB1) were also used to validate the SSC-like cell identity. Results Proliferation of SSCLCs was achieved. The presence of SSCs in SSCLCs was confirmed by positive immunostaining of LIN28, UCHL1 and quantitative polymerase chain reaction for LIN28A, UCHL1, PLZF, ITGA6, and ITGB1, respectively. Conclusion This study has demonstrated that SSCs from infant boys possess the capacity for in vitro proliferation and advance a fertility preservation strategy for pre-pubertal boys who may otherwise lose their fertility.